ON THE IMPORTANCE OF MANAGERIAL AND ORGANISATIONAL VARIABLES IN THE QUANTITATIVE RISK ASSESSMENT - Milazzo, Maria Francesca (Journal of Applied Engineering Science, 2016)
Common practises for Quantitative Risk Assessment (QRA) include the estimation of frequencies of releases and related initial causes; these are a function of several parameters such as components failure rates, probabilities of human error, equipment damage and managerial factors. The availability of general values for such parameters from the literature simplifies the work of the risk analyst, but standardised results are provided, which unfortunately do not permit taking into consideration the plant’s specificity. The specificity of the establishment is defined through its management system, thus if managerial and organisational factors are neglected or not proper assessed, risk analysis for two identical establishments, characterised by totally different management systems, gives the same results and this appears absolutely unacceptable especially when risk analysis is used for risk-based decisions. This paper aims quantifying the effects of managerial and organisational variables on the frequency of losses of containment of pipeworks, by using a simple and flexible method developed by Milazzo and co-authors in 2010. Such a methodology has been tested on a new case-study and the results of the assessment have been evaluated from both the sensitivity and uncertainty points of view. An application has been shown with respect to the alkylation unit of a refinery.